2019
DOI: 10.1101/679563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maltotriose consumption by hybridSaccharomyces pastorianusis heterotic and results from regulatory cross-talk between parental sub-genomes

Abstract: S. pastorianus strains are hybrids of S. cerevisiae and S. eubayanus that have been domesticated for several centuries in lager-beer brewing environments. As sequences and structures of S. pastorianus genomes are being resolved, molecular mechanisms and evolutionary origin of several industrially relevant phenotypes remain unknown. This study investigates how maltotriose metabolism, a key feature in brewing, may have arisen in early S. eubayanus × S. cerevisiae hybrids. To address this question, we generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 86 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…This data set confirms the previously proposed population structure (Peris et al 2014(Peris et al , 2016Eizaguirre et al 2018), where two major populations were detected (Patagonia A/Population A/PA and Patagonia B/Population B/PB), which has been further divided into five subpopulations (PA-1, PA-2, PB-1, PB-2 and PB-3) (Eizaguirre et al 2018). Other isolates from outside Patagonia belong to PB, either the PB-1 subpopulation that is also found in Patagonia (Gayevskiy and Goddard 2016;Peris et al 2016), or a Holarctic-specific subpopulation (PB-Holarctic) that includes isolates from Tibet and from North Carolina, USA (Bing et al 2014;Peris et al 2016;Brouwers et al 2019), which represents the closest known wild relatives of the S. eubayanus subgenomes of lager-brewing yeasts (Bing et al 2014;Peris et al 2016). Furthermore, heterosis was recently demonstrated in a S. cerevisiae x Tibetan S. eubayanus hybrid, which showed that regulatory cross talk between the two subgenomes is partly responsible for maltotriose and maltose consumption (Brouwers et al 2019).…”
Section: Genomic Insights Into the Fascinating Phylogeography Of The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This data set confirms the previously proposed population structure (Peris et al 2014(Peris et al , 2016Eizaguirre et al 2018), where two major populations were detected (Patagonia A/Population A/PA and Patagonia B/Population B/PB), which has been further divided into five subpopulations (PA-1, PA-2, PB-1, PB-2 and PB-3) (Eizaguirre et al 2018). Other isolates from outside Patagonia belong to PB, either the PB-1 subpopulation that is also found in Patagonia (Gayevskiy and Goddard 2016;Peris et al 2016), or a Holarctic-specific subpopulation (PB-Holarctic) that includes isolates from Tibet and from North Carolina, USA (Bing et al 2014;Peris et al 2016;Brouwers et al 2019), which represents the closest known wild relatives of the S. eubayanus subgenomes of lager-brewing yeasts (Bing et al 2014;Peris et al 2016). Furthermore, heterosis was recently demonstrated in a S. cerevisiae x Tibetan S. eubayanus hybrid, which showed that regulatory cross talk between the two subgenomes is partly responsible for maltotriose and maltose consumption (Brouwers et al 2019).…”
Section: Genomic Insights Into the Fascinating Phylogeography Of The ...mentioning
confidence: 99%
“…Other isolates from outside Patagonia belong to PB, either the PB-1 subpopulation that is also found in Patagonia (Gayevskiy and Goddard 2016;Peris et al 2016), or a Holarctic-specific subpopulation (PB-Holarctic) that includes isolates from Tibet and from North Carolina, USA (Bing et al 2014;Peris et al 2016;Brouwers et al 2019), which represents the closest known wild relatives of the S. eubayanus subgenomes of lager-brewing yeasts (Bing et al 2014;Peris et al 2016). Furthermore, heterosis was recently demonstrated in a S. cerevisiae x Tibetan S. eubayanus hybrid, which showed that regulatory cross talk between the two subgenomes is partly responsible for maltotriose and maltose consumption (Brouwers et al 2019). Multilocus data suggested that two more lineages from China, West China and Sichuan, diverged very early from all other known S. eubayanus strains, while Holarctic isolates from China had unusually low sequence diversity (Bing et al 2014).…”
Section: Genomic Insights Into the Fascinating Phylogeography Of The ...mentioning
confidence: 99%
“…Recent studies on novel S. cerevisiae x S. eubayanus hybrids suggest that hybrid fermentative vigour at low temperature results from a variety of genetic changes, including loss of heterozygosity (LOH), ectopic recombination, transcriptional rewiring, selection of superior parental alleles (Sipiczki, 2018), heterozygote advantage due to the complementation of loss-of-function mutations in the F1 hybrid genome (Brouwers et al, 2019), and novel structural and single nucleotide variants in the hybrid genome (Krogerus, Holmström, et al, 2018). A recent transcriptome analyses of a laboratory-made Lager hybrid strain under fermentation conditions highlighted that the regulatory 'cross-talk' between the parental subgenomes caused a novel sugar consumption phenotype in the hybrid (maltotriose utilization, essential for Lager fermentation), which was absent in both parental strains (Brouwers et al, 2019). Although these studies have greatly contributed to our understanding of the genetic basis of different lager phenotypes, most studies only considered a single S. eubayanus genetic background (type strain CBS 12357), which alone is not representative of the species-rich genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evolution with microbes is a powerful tool to study adaptive responses to selection under environmental constraints (Barrick & Lenski, 2013; Cooper, 2018; Maddamsetti et al, 2015; Payen & Dunham, 2016). Recent studies on novel S. cerevisiae x S. eubayanus hybrids suggest that hybrid fermentative vigour at low temperature results from a variety of genetic changes, including loss of heterozygosity (LOH), ectopic recombination, transcriptional rewiring, selection of superior parental alleles (Sipiczki, 2018), heterozygote advantage due to the complementation of loss-of-function mutations in the F1 hybrid genome (Brouwers et al, 2019), and novel structural and single nucleotide variants in the hybrid genome (Krogerus, Holmström, et al, 2018). A recent transcriptome analyses of a laboratory-made Lager hybrid strain under fermentation conditions highlighted that the regulatory ‘cross-talk’ between the parental subgenomes caused a novel sugar consumption phenotype in the hybrid (maltotriose utilization, essential for Lager fermentation), which was absent in both parental strains (Brouwers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The creation of novel lager yeast strains through artificial crosses between S. cerevisiae and S. eubayanus has shown the added value of the association, especially in the context of low-temperature lager brewing. Improvements include greater tolerance of low temperatures, the ability to utilize maltotriose efficiently, and strong flocculation potential (Alexander et al 2016;Brouwers et al 2019a;Hebly et al 2015;Krogerus et al 2015Krogerus et al , 2017Mertens et al 2015), all of which are necessary for successful lager fermentation. The ability to grow and ferment at low temperatures appears to be the main characteristic inherited from the cold-tolerant S. eubayanus.…”
Section: Introductionmentioning
confidence: 99%